The leaching of gold, silver and their alloys in alkaline glycine–peroxide solutions and their adsorption on carbon - Oraby, E; Eksteen, Jacques (Elsevier, 2015)
The leaching of gold and silver in a pH modified glycine solution in the presence of hydrogen peroxide was investigated. It was found that this lixiviant system can dissolve gold and/or silver under neutral and alkaline conditions at ambient to moderately elevated temperatures (23–60 °C). The gold leaching rate in solutions containing 0.5 M glycine and 1% peroxide at pH 11 after 48 h of leaching was found to be 0.322 μmol/m2 s, which is comparable to gold leaching rate after six days in thiosulphate–EDTA or thiosulphate–oxalate systems in the presence of thiourea (0.22–0.25 μmol/m2 s). In alkaline glycine–hydrogen peroxide solutions, it has been found that gold leach rate from gold–silver (50% Ag) alloy is about 6 times higher than rate from pure gold and the silver leach rate was 0.247 μmol/m2 s. An induction period of 48 h was noted for rolled precious metal foils, after which leaching rapidly accelerated. The reaction rate sensitivity to temperature can be explained by a mechanism that is chemical reaction controlling rather than mass transfer controlling as found for cyanide leaching. Precious metal dissolution rates increased with increased glycine concentration, increased silver content, and increasing pH (up to pH 11). The gold–glycinate complex was found to effectively load on activated carbon up to 13.2 g Au/kg carbon in 4 h.